The Effect of Self-Care Education on Quality of Life in Unstable Angina Patients in Kashan Shahid Behashti Hospital, 2011 - Neda Mirbagher Ajorpaz; Mahboube Kafaei Atrian (Golestan University of Medical Sciences, 2014)
Background and Objective: Unstable angina (UA) patients account for more than half of hospitalized patients in CCU. Very often, re-hospitalization of these patients is due to lack of enough information and compliance with medical advice, having negative effect on quality of life. Thus, we aimed to determine the effect of self-care education on quality of life in unstable angina patients in Kashan Shahid Behashti hospital in 2010. Material and Methods: This quasi-experimental study was conducted on 80 unstable angina patients divided randomly into control and intervention group. The instruments were demographic and quality of life questionnaire (SF36), used before and after intervention. For intervention group, we carried out two face-to-face 2-hour sessions. The first session was performed at admission and the second at the time of discharge with the presence of patient's family. Finally, the two groups were compared and analyzed by SPSS 14 version, using paired t test and independent t test. Results: The results in two groups showed that there were significant differences in dimensions including General health, physical health, mental health, social function, limitation in activities, and vitality (p≤0.05). But the difference was not significant for health changes and body pain. Conclusion: Nurse follow-up and patient-centered self-care education can be useful for improving quality of life in unstable angina patients.